Aggregation of Rabbit Blood Platelets Produced in Vitro by Saline “Extract” of Tendons - Hovig, Torstein (Thrombosis and Haemostasis, 1963)
Rabbit blood platelet aggregates were produced in vitro by addition of rabbit tendon “extract” to citrated platelet-rich plasma. The aggregating activity was not due to presence of adenosine diphosphate in the “extracts” and was unrelated to blood coagulation. The aggregating principle was destroyed by heating of the “extract” to 60° C for 15 minutes or by incubation with collagenase for 1 hour at 37° C. The aggregating effect was associated with particles which were sedi- mented by centrifugation for 30 minutes at 10,000 G. By means of electron microscopy the particles were identified as cross-striated collagen fibrils.